Evaluating Fiscal Equalization in Indonesia - Hofman, Bert; Kadjatmiko; Kaiser, Kai; Suharnoko Sjahrir, Bambang (World Bank, Washington, DC, 2012)
This paper presents a methodology to evaluate fiscal decentralization focusing on the potential mis-targeting of intergovernmental fiscal equalization transfers. The approach builds on an explicit comparison and the summary measurement of different (horizontal) allocation distributions across states or localities. Whereas formula-based fiscal transfers have the merit of being transparent and promoting revenue predictability in fiscal decentralization, in practice, two challenges emerge: (1) What are the appropriate formula designs given the sub-national data constraints evident in most decentralizing developing countries? and (2) How costly in terms of mis-targeting to the presumed expenditure needs and fiscal capacity are deviations from these types of benchmark formulas (for example, due to historical factors or the need to meet establishment costs such as civil service wages)? The authors illustrate this approach by assessing Indonesia's evolving intergovernmental fiscal system instituted in the 2001 Big Bang decentralization. The discussion comes against Indonesia's recent policy decision to fully fund sub-national civil servant wages as part of the base general allocation grant (DAU) transfers, raising questions about both incentive effects for local governments and potential mis-targeting. The authors identify potential efficiency losses from the DAU's horizontal misallocation from half a dozen alternative scenarios found in the policy dialogue, ranging from 9 to 30 percent-on the order of US$ 3.9 billion-of the overall annual size of this large intergovernmental transfer. The scale of these tradeoffs highlights the importance of intergovernmental transfers in more general debates in public finance for decentralized countries.